2006
DOI: 10.1364/oe.14.007678
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive white-light spectral interferometry with absolute phase retrieval to measure thin film

Abstract: Abstract:We present a white-light spectral interferometric technique for measuring the absolute spectral optical path difference (OPD) between the beams in a slightly dispersive Michelson interferometer with a thin-film structure as a mirror. We record two spectral interferograms to obtain the spectral interference signal and retrieve from it the spectral phase, which includes the effect of a cube beam splitter and the phase change on reflection from the thin-film structure. Knowing the effective thickness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 18 publications
0
62
0
1
Order By: Relevance
“…The reflectance and interferometric phase (nonlinear-like phase [10,11]) of a thin-film structure, which are measured in a slightly dispersive Michelson interferometer at the same time and which agree very well with theory, are used to determine precisely thickness of the SiO 2 thin film on silicon wafers of two crystallographic orientations and different dopant concentrations. We revealed that the thin-film thickness, which varies with the type of silicon substrate, depends linearly on the wavelength at which minimum in the spectral reflectance occurs.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…The reflectance and interferometric phase (nonlinear-like phase [10,11]) of a thin-film structure, which are measured in a slightly dispersive Michelson interferometer at the same time and which agree very well with theory, are used to determine precisely thickness of the SiO 2 thin film on silicon wafers of two crystallographic orientations and different dopant concentrations. We revealed that the thin-film thickness, which varies with the type of silicon substrate, depends linearly on the wavelength at which minimum in the spectral reflectance occurs.…”
Section: Introductionmentioning
confidence: 82%
“…The procedure for the interferometric measurement [10,11] is based on recording the spectral interferograms in a dispersive Michelson interferometer with one of its mirrors replaced by a thin-film structure and retrieving the absolute optical path difference (OPD) ∆(λ). The OPD ∆(λ) is used to construct for a chosen mirror position L = L 0 the nonlinear-like phase function δ(λ) given by the relation (2) where t eff is the effective thickness of a beam splitter cube [9][10][11] and δ 2 (λ) is the phase change on reflection from the mirror in the interferometer.…”
Section: Methods Of Spectral Interferometrymentioning
confidence: 99%
See 3 more Smart Citations